Comparative analysis of pigtail catheter versus intercostal tube drainage for pleural effusion: a tertiary centre study - Khare, Rahul; anand, Krishnanand; Agrawal, Puneet; Yadav, Anand (International Surgery Journal, 2022)
Background: This study was conducted to compare the effectiveness and complications between chest tube and pigtail catheter thoracostomy for drainage of pleural effusion. Methods: We retrospectively reviewed the medical records of 60 patients with pleural effusion during the period of January 2021 to June 2022. We collected data on fluid drainage, complications, and hospital stays among participants. Results: The difference between various parameters (protein, sugar, pH, and culture positive) measured on drained pleural fluid was statistically nonsignificant (p>0.5). A total of 4 (13.3%) and 2 (6.7%) cases were not drained in the intercoastal tube and pigtail catheter groups, respectively (p=0.389). Further, a total of 14 (46.7%) and 6 (20%) participants in the intercoastal tube and pigtail catheter groups respectively complained of wound pain (p=0.028). Lastly, the incidence of complications among the participants in the intercoastal tube and pigtail catheter groups was 30% and 16.7% (p=0.222). The most common complications in both groups were pneumothorax. Moreover, a total of 10% of participants in the intercoastal tube group experienced kinking or dislodgment of the tube. The duration of hospital stay was significantly shorter among participants with pigtail catheters. Conclusions: The pigtail catheter was equally efficacious as an intercoastal tube, but it caused lower pain, shorten the duration of hospital stay, and reduced the complications among participants.